Expert systems the technology of knowledge management and decision making for the 21st century - Leondes, Cornelius T. (San Diego : Academic Press, 2002)
This six-volume set presents cutting-edge advances and applications of expert systems. Because expert systems combine the expertise of engineers, computer scientists, and computer programmers, each group will benefit from buying this important reference work. An "expert system" is a knowledge-based computer system that emulates the decision-making ability of a human expert. The primary role of the expert system is to perform appropriate functions under the close supervision of the human, whose work is supported by that expert system. In the reverse, this same expert system can monitor and double check the human in the performance of a task. Human-computer interaction in our highly complex world requires the development of a wide array of expert systems. Key Features * Expert systems techniques and applications are presented for a diverse array of topics including: * Experimental design and decision support * The integration of machine learning with knowledge acquisition for the design of expert systems * Process planning in design and manufacturing systems and process control applications * Knowledge discovery in large-scale knowledge bases * Robotic systems * Geograhphic information systems * Image analysis, recognition and interpretation * Cellular automata methods for pattern recognition * Real-time fault tolerant control systems * CAD-based vision systems in pattern matching processes * Financial systems * Agricultural applications * Medical diagnosis.
VOLUME 1 -- History and Applications -- Tools and Applications -- Development and Applications of Decision Trees -- Reasoning with Imperfect Information -- Experimental Design and Decision Support -- A Model-Based Expert System Based on a Domain Ontology -- Intelligent System Control: A Unified Approach and Applications -- Real Time Fault-Tolerant Control Systems -- VOLUME 2: -- Model of Reasoning with Conflicting Information Sources in Knowledge-Based Systems -- Process Planning in Design and Manufacturing Systems -- Intelligent Systems Techniques and Their Applications in Manufacturing Systems -- Architecture, Engineering and Construction (AEC) Design -- Neural Networks for Process Control Application to the Temperature Control of Batch Chemical Reactors -- Intelligent Tools and Their Applications in Geographic Information Systems -- Microprocessor Systems -- Scheduling Systems for Shipbuilding -- VOLUME 3 -- Genetic Image Interpretation -- Automated Visual Assembly Inspection -- Multiresolution Invariant Image Recognition -- Image Processing for Automatic Roads Determination -- Automated Visual Inspection Systems -- Visual Programming Technology in Expert Systems Development -- CAD-Based Vision Systems in Pattern Matching Process -- Cellular Automata Architectures for Pattern Recognition -- Machine Intelligent Systems Techniques for Automatic Harvest System -- Integrating Machine Learning with Knowledge Acquisition -- Modeling Human Reasoning Processes Under Uncertain Conditions -- VOLUME 4 -- Devising an Expert System for Pediatric Syndrome Diagnosis -- Knowledge Discovery in Larger Scale Knowledge Databases -- Efficient Data Utilization -- Investment Decision Making -- Intelligent Systems Control in Manufacturing Cells -- Knowledge-Based Approach for Automating Web Publishing from Databases -- Neural Networks for Economic Forecasting Problems -- Determination of Principal Components in Data -- Time Series Prediction -- VOLUME 5 -- Hybrid Expert Systems: An Approach to Combining Neural Computation and Rule-Based Reasoning -- POPFNNS: Fuzzy Neural Techniques for Rule-Based Identification in Expert Systems -- Preventive Quality Management -- Neuro-Fuzzy Systems -- Knowledge Representation by Means of Multi-Layer Perceptrons -- A Guide to Research in Assumption-Based Truth Maintenance Systems (ATMS) in Constraint Satisfaction -- A Method for Utilization of Previous Experience in Designing Expert Systems -- Model-Based Process Fault Diagnosis -- VOLUME 6 -- Automation of Concept Development -- A Methodology for Building Case-Based Reasoning Systems in Ill-Structured Optimization Domains -- The Trainor System: Applying QR Techniques to Intelligent Tutoring Systems -- Structuring Expert Control Using the Integrated Process Supervision Architecture -- TAP: An Inquiry Teaching Shell Using both Rule-Based and State-Space Approaches -- Self Teaching and Exploratory Task-Learning Methods in Unknown Environments and Applications in Robotic Skills.
Includes bibliographical references and index.
Keywords: Expert systems (Computer science).; Electronic books